Effect of sample thinning on strains and lattice rotations measured from Transmission Kikuchi diffraction in the SEM - Karamched, PS; Saravanan, N; Haley, JC; Wilkinson, AJ; Lozano-Perez, S (Elsevier, 2021)
Cross correlation based high angular resolution EBSD (or HR-EBSD) has been developed for measurement of elastic strains, lattice rotations (and estimating GND density). Recent advances in Transmission Kikuchi diffraction (TKD), especially the on-axis geometry allows the possibility of acquiring patterns at higher spatial resolution. However, some controversy remains as to whether stresses/strains measured after the sample thinning process are still representative of the bulk sample. In this paper, we explore a way of applying the HR-EBSD method to study strains and lattice rotations in an initially bulk sample, that is then progressively thinned down until a similar analysis can be performed on thin (and electron transparent) samples. Thus, HR-TKD will be compared as a possible alternative to HR-EBSD, in scenarios when it is not always possible to perform EBSD on the surface of the sample. An estimate of strain relaxation in the sample as a result of sample thinning is presented.